2015
DOI: 10.1111/aor.12521
|View full text |Cite
|
Sign up to set email alerts
|

The Hemodynamic Effects of Hemodialysis Needle Rotation and Orientation in an Idealized Computational Model

Abstract: Maintaining the patency of vascular access is essential for performing efficient hemodialysis. Appropriate cannulation technique is critical in maintaining the integrity of vascular access. This study focused on analyzing the hemodynamic effect of needle rotation, which is performed to alleviate the pressure if the needle becomes attached to the blood vessel wall. The hemodynamic benefits (normal wall shear stress [WSS] and smooth flow with no oscillatory motion) of this technique are investigated in an ideali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Vessel injury promotes inflammation as described above as well as platelet adhesion, which propagates inflammation and promotes thrombosis. 112,113 Area cannulation and retrograde direction of the arterial needle with bevel down were associated with higher risk of AVF failure in a study by Parisotto et al 114 Furthermore, the presence of needles in the AVF might contribute to abnormal WSS, as reported by Fulker et al, [115][116][117] with antegrade orientation of the arterial needle producing a larger area of oscillatory shear stress. Higher turbulent flow downstream of the venous needle and consequent endothelial dysfunction and loss of NO expression have been described.…”
Section: Vessel Injurymentioning
confidence: 88%
“…Vessel injury promotes inflammation as described above as well as platelet adhesion, which propagates inflammation and promotes thrombosis. 112,113 Area cannulation and retrograde direction of the arterial needle with bevel down were associated with higher risk of AVF failure in a study by Parisotto et al 114 Furthermore, the presence of needles in the AVF might contribute to abnormal WSS, as reported by Fulker et al, [115][116][117] with antegrade orientation of the arterial needle producing a larger area of oscillatory shear stress. Higher turbulent flow downstream of the venous needle and consequent endothelial dysfunction and loss of NO expression have been described.…”
Section: Vessel Injurymentioning
confidence: 88%
“…A study involving 48 patients found greater pain severity and a larger hole left by the needle when the bevel was facing upwards [ 21 ], which appears to be confirmed by a study in 70 patients finding a lower risk of bleeding during cannulation when the bevel is facing downwards [ 22 ]. Modelling the flows and pressures did not reveal any relationship between the position of the bevel and dialysis dose [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A fully structured hexahedral grid was created in ICEM 14.5 (ANSYS, Inc., Canonsburg, PA, USA), consisting of ∼8 million cells. A previous grid independence analysis found a maximum variation of peak WSS of 3.1% using this grid size . Computational simulations were conducted in Fluent 14.5 (Fluent, Inc., Lebanon, NH, USA) under the assumption of non‐compliant walls due to the arterialization of the cephalic vein after AVF creation.…”
Section: Methodsmentioning
confidence: 99%